Of Seeds and Snow: Climate, Culture, and Collaborative Environmental History on the Hopi Mesas. - Johnson, Tai Elizabeth (Transactions of the American Philosophical Society, 2025)
The article focuses on the impact of climate change and prolonged drought on Hopi agriculture and food systems in northern Arizona. It details how the Hopi people, who have cultivated their land for over a thousand years, are experiencing significant shifts in weather patterns, including reduced snowfall and altered monsoon rains, which are critical for their traditional farming practices. Through oral histories collected from Hopi farmers and gardeners, the article highlights the cultural and ecological challenges they face, including crop failures, diminished biodiversity, and the psychological effects of climate change on their community. The narrative emphasizes the resilience of the Hopi people as they adapt their agricultural practices in response to these environmental changes while maintaining their cultural heritage.